Pattern of Presentation of Moyamoya Disease (MMD) Patients in Bangladesh: Experience from Tertiary Care Hospitals - Khan, Sharif Uddin; Rahman, Kazi Mohibur; Hasan, ATM Hasibul; Islam, Sirajee Shafiqul; Chowdhury, Rajib Nayan; Patwary, Md Khairul Kabir; Elyas, Dewan Mohammad; Khan, Abdul Momen; Hossain, Md Amir; Azam, Md Bokhtiar; Hasanat, Md Amirul (Bangladesh Journal of Neuroscience, 2017)
Background: Moyamoya disease is rare but not uncommon throughout the world. Clinical profile of childhood moyamoya (MMD) disease is not well delineated in Bangladesh. Methods: We conducted this cross sectional study in pediatrics and neurology department of Dhaka Medical College Hospital that involved 20 patients of MMD over a period of one year. Result: Among the cases about 2/3rd(65%) of the patients were within 8 years age at onset with mean age of the patients being 7.24(±3.34) years at onset with a male: female ratio of 1.2:1. Almost half of the patients had past history of intermittent episodes TIA which precipitated by hyperventilation and crying (p <0.05). Important history related to prothombotic conditions (Family History of stroke, MI, Hyperlipidemia, Obesity, Coagulation disorders) were also statistically significant (p<0.05). Sixteen patients in our series exhibited hemiparesis and out of them 4(25%) were alternating (p<0.05), followed by dysarthria at onest 13(65%). Convulsions and visual impairment were seen in 5 (25%) different patients, 3(15%) different patients had altered consciousness, involuntary movements, ataxia, headache and cognitive impairment at onset. We observed intellectual impairment in and psycho–motor retardation in two different patients. MRA abnormalities were found in 19 cases out of 20. Among 19 cases bilateral ICA stenosis with collaterals seen in 18 cases (90%), MCA stenosis along with bilateral ICA stenosis were seen in 16(80%) cases, ACA stenosis along with bilateral ICA stenosis were seen in 07(35%) cases, PCA stenosis along with bilateral ICA stenosis were observed in 05(25%) cases. No collaterals and without typical “puff of smoke” appearance was seen in 01(5%) and unilateral ICA stenosis with collaterals was seen in 01(5%) cases (probable MMD). Diagnostic Cerebral DSA was done in 07 (35%) patients and typical angiographic findings of Moyamoya disease were present in all of them. Conclusion: C-MMD may have various presentations. Stroke and TIA are most common presentation. MRA may well delineate the characteristics angrographic abnormality. Bangladesh Journal of Neuroscience 2017; Vol. 33 (1): 24-29